Using Delphi technique to build consensus in practice - Lefkothea Giannarou; Efthimios Zervas (International Journal of Business Science & Applied Management (IJBSAM), 2014)
This paper focuses on the use of Delphi technique in building consensus in practice. More specifically, it reviews some fuzzy issues regarding the expert's panel selection and the questionnaire design, while it provides two case examples for the consensus measurement. Hence, examining some controversies, it makes obvious that the purpose of the study and the homogeneity of the sample are crucial factors when designing the Delphi procedure. However, what still remains unclear is the approach in measuring consensus, which varies from study to study. In this case, the present paper recommends a complementary use of three measures to assess consensus, since each one separately could not be thought of as a good proxy of it. These measures are: (i) the interquartile range, (ii) the standard deviation and (iii) the 51% percentage of respondents lying in the 'highly important' or "strongly agreeing" category.
Keywords: 650; Delphi method; methodological problems; consensus building; application; research guidelines